Asociaciones Público Privadas en transporte y su impacto en la economía del Perú, periodo 1999-2017 - Vergara Quesquén, Ingrid Pamela (2019)
This research is entitled “Public Private Partnerships in transport and its impact on the economy of Peru, period 1999-2017 ”and seeks to determine the impact of public-private investment in transportation infrastructure in the Peruvian economy during the study period, considering an econometric model of Ordinary Minimum Squares, for which statistical information from the following institutions was used : National Institute of Statistics and Informatics (INEI), Ministry of Economy and Finance (MEF), PROINVERSION, Central Reserve Bank of Peru (BCRP) and Organization for Economic Cooperation and Development (OECD), which were transformed at prices constants of 2007 in per capita terms and corrected for purchasing power parity. Likewise, information was obtained from OSITRAN, CORPAC and SUNAT to know the performance of PPPs. The results showed that public-private investment in transport infrastructure has a positive impact on the Peruvian economy during the period 1999 to 2017, because it contributes substantially and significantly to the economic growth of the country, corresponding to a greater contribution compared to the public investment, this because a greater public-private investment in 1%, generates an increase in 0.02% of the economic growth of the country.